STRATEGIES FOR IMPROVING ARABIC LANGUAGE SKILLS AT THE IBADURRAHMAN PUTRI ISLAMIC BOARDING SCHOOL IN STABAT, NORTH SUMATRA - Nisa, Khairun (Al-Mubin, 2025)
Speaking skills are one of the main skills in mastering Arabic, which remains a challenge in the pesantren environment, especially for female students who come from a background where their mother tongue is not Arabic. The Ibadurrahman Putri Stabat Langkat Islamic Boarding School implements various familiarization strategies to improve the Arabic speaking skills Arabic speaking skills of female students. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The purpose of this study is to describe the habit-forming strategies implemented by the boarding school and evaluate their effectiveness in creating a language environment that supports the process of acquiring speaking skills. The results of the study indicate that strategies such as the use of Arabic by female teachers, intensive training for new students during the first three months, daily vocabulary memorization, the implementation of tahkim and muhawarah, the prohibition of using local languages, as well as regular musyahadah and classroom vocabulary activities, are effective in increasing the students activity, confidence, and vocabulary mastery in Arabic communication. These strategies not only create a lively and structured language environment, but also psychologically shape the motivation and confidence of female students to use Arabic in their daily lives. The conclusion of this study is that language habit formation through integrated and consistent strategies has proven effective in improving the Arabic speaking skills of female students in the pesantren environment